(3GdLGeY GdUMjMs - (3eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, CHh YHO Gddg , J (B256 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdCOH HGH bhd Gddg YR hLd (B: (3hhUjfG GdEfSGf HhGdOjg s
(3BNQgG (B:s
(3bGd GdfHi Udi Gddg Ydjg hSde cdeJGf MHjHJGf Zdi GdQMef NajaJGf Ydi GddSGf KbjdJGf ai GdejRGf SHMGfg Gddg hHMeOg SHMGf Gddg GdYXje Je GdSaQ GdNGeS s
(3GdfSNI HgG MhGTs
(3ef fSNI GHf SYGOI GdSGHbI hHg JeGe GdUMjMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdMOjK h GdeUWdMs